Digital Transformation: A Solution for Accounting Recording at Kampoeng Tenun Alor MSME in Kupang City - Pah, Viany Cecilia; Pane, Ayu Sartika (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Reliable accounting information is essential for Micro, Small, and Medium Enterprises (MSMEs) as it forms the basis for decision-making and business management. It supports activities such as business expansion, pricing, and performance evaluation. However, most MSMEs in Kupang City do not maintain proper accounting records due to limited knowledge, a small customer base, and the perception that small-scale businesses do not require structured accounting.This study aims to improve MSMEs’ understanding and ability to conduct proper accounting through digital recording systems. The selected research subject is Kampoeng Tenun Alor (KTeA), a local weaving MSME in Kupang. The study uses the Participatory Action Research (PAR) method, starting with identifying research problems faced by KTeA MSMEs, collecting information from KTeA Business Actors to answer the research questions, analyzing and interpreting the information provided by KTeA MSMEs, and providing a solution to participants: a Financial Reporting application for KTeA MSMEs.The research results show that after five testing phases, each software function effectively met KTeA’s operational needs. Thus, the application can assist in daily operations and generate financial reports. Future research is expected to design more advanced, computer-assisted accounting techniques and synchronize them with broader accounting systems.